IJCM_313A: Assessment of the health-related quality of life among ex-mine workers of Kolar gold fields, Kolar, Karnataka - George Jobin; Sachin KV; Joy George; Joseph Bobby; Ramesh Naveen (Wolters Kluwer Medknow Publications, 2024)
Background: Karnataka ranks third with regards the number of mines in India and Kolar, at one time, had the world's deepest and most productive gold mines. Miners are exposed to hazardous agents like silica, coal and asbestos which adversely impact health. Objectives: To assess the health-related quality of life (HRQL) of ex-mine workers at Kolar Gold Fields (KGF), Kolar, Karnataka. Methodology: An analytical cross-sectional study was conducted among 240 (estimated 196 with 50% prevalence) male ex-mine workers of KGF. An interview scheduled, consisting of socio-demographic factors, COPD Assessment Test (CAT) and Kings Brief Interstitial Lung Disease (KBILD) was administered. Lower CAT score and higher KBILD score indicate better HRQOL. Results: The mean age of the participants was 69.71±8.56 years. Participants were previously involved in drilling (113-47%) and blasting (127-53%) activities in the mines, with a mean of 14.68±6.46 years of work exposure. The mean scores for CAT and KBILD were 15.80±7.42 and 52.83±8.77 respectively. Based on CAT scores, half (51%) of participants reported medium impact of COPD on their health. Participants with longer duration of work experience had significantly higher CAT scores [OR-36.64 (12.14-110.6)]. KBILD score was significantly higher among those who worked in blasting (M=113. SD=52.14) than those involved in drilling (M=127, SD=53.43). Lower duration of work was significantly associated with higher KBILD scores (p<0.01). Adjusted logistic regression showed higher education and income had a positive impact on HRQL and an increase in age and longer work experience adversely affected HRQL. Conclusion: This study reveals the hazardous impact of drilling and blasting work on the health-related quality of life of ex-mine workers. Understanding this, for the future, it is important to educate workers, improve financial stability and minimize hazard exposure to enhance the quality of life of miners amidst the challenges of mining operations.